2017
DOI: 10.1111/1095-9270.12276
|View full text |Cite
|
Sign up to set email alerts
|

The Ereğli E Shipwreck, Turkey: an early Hellenistic merchant ship in the Black Sea

Abstract: A shipwreck from the early 3rd century BC was discovered in the Black Sea's suboxic depths off Ereğli, Turkey, during the 2011 E/V Nautilus expedition. Remote investigation revealed the trawl‐damaged remains of a merchant ship carrying multiple amphora types associated with Aegean and Pontic production areas. Also discovered were elements of the ship's hull that show evidence of both pegged mortise‐and‐tenon and laced construction. The wreck provides crucial archaeological evidence for both maritime connectivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…, ; Davis et al. , ) shows that the Greek tradition of sewn boats did not suddenly vanish with the final developments evidenced by the Kyrenia wreck.…”
Section: The Greek Tradition: a Survivalmentioning
confidence: 99%
See 2 more Smart Citations
“…, ; Davis et al. , ) shows that the Greek tradition of sewn boats did not suddenly vanish with the final developments evidenced by the Kyrenia wreck.…”
Section: The Greek Tradition: a Survivalmentioning
confidence: 99%
“…At the start of the 3rd century BC, contemporary to or slightly later than the Kyrenia wreck, the Eregli E wreck, recently discovered in the Black Sea (Brennan et al, 2013;Davis et al, 2018) shows that the Greek tradition of sewn boats did not suddenly vanish with the final developments evidenced by the Kyrenia wreck.…”
Section: The Greek Tradition: a Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…The exclusion of oxygen may also affect the rate of decay of DNA on marine archaeological sites as cytosine deamination involves the addition of an oxygen molecule (March, 1977), and bacterial diagenesis will be significantly slowed in an anoxic environment. The newly discovered ancient shipwrecks of the Black Sea exhibit exceptional preservation of organic material due to the anoxic seawater environment that exists there (Davis et al, 2018;Markey, 2003), and it is possible that these sites will offer outstanding DNA preservation. In addition, early research into DNA depurination showed that there was a clear 'salt effect' in samples incubated in high ionic environments; the 'salt effect' significantly slowed the process of depurination in these samples (Lindahl and Nyberg, 1972).…”
Section: Dna and The Marine Environmentmentioning
confidence: 99%
“…The methodology and aims of maritime archaeology have seen significant shifts in recent decades as the quality of remote imaging has improved and the time, costs and storage needs associated with large-scale excavation have become prohibitive. Carefully selected sampling and imaging of wrecks (Demesticha 2011;Tereschenko 2013;Davis et al 2018;Koutsouflakis 2017a;2017b; 2018; Vidličková 2019) has largely replaced complete excavation of single sites (Carlson and Aylward 2010;Lawall 2011c;Carlson 2013) (Fig. 132).…”
Section: Distribution and Marketsmentioning
confidence: 99%